Fostering Entrepreneurship by Linking Organizational Unlearning and Innovation: The Moderating Role of Family Business - Leal-Rodríguez, Antonio; Peris-Ortiz, Marta; Leal-Millán, Antonio (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
Innovation is a key component of entrepreneurship and is considered crucial for achieving sustainable competitive advantage. The research model in this paper empirically explores the link between organizational unlearning and innovation outcomes. The model assesses the moderating influence of family business ownership on this link. Hypotheses were tested using a sample of 145 firms in the Spanish automotive components manufacturing sector. Relationships between the constructs were assessed using partial least squares (PLS) SEM path modeling. Results show the significant positive effect of organizational unlearning on the firm’s innovation outcomes.